2022
DOI: 10.3389/fpubh.2022.990620
|View full text |Cite
|
Sign up to set email alerts
|

Patient-centered care and patient satisfaction: Validating the patient-professional interaction questionnaire in China

Abstract: ObjectiveTo introduce patient-centered approach in China and to relate it with Chinese patient satisfaction via validating the Chinese version of Patient-Professional Interaction Questionnaire (PPIQ-C).DesignThis cross-sectional survey was conducted through face-to-face interviews from June to September in 2019. Participants rated their patient-centered care experience via the 16-item translated PPIQ, their experience of the received medical service, and their overall satisfaction.SettingKunshan Huaqiao People… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…OCB can improve the quality of service by facilitating the achievement of hospital goals and improving the performance of doctors. This is reflected in more efficient medical personnel services and improved relationships with patients and medical personnel (Han et al, 2018). Therefore OCB affects social capital; where communication and behavior greatly affect the relationship between employees and customers (Jafari et al, 2020).…”
Section: Multiple Linear Regression Analysismentioning
confidence: 99%
“…OCB can improve the quality of service by facilitating the achievement of hospital goals and improving the performance of doctors. This is reflected in more efficient medical personnel services and improved relationships with patients and medical personnel (Han et al, 2018). Therefore OCB affects social capital; where communication and behavior greatly affect the relationship between employees and customers (Jafari et al, 2020).…”
Section: Multiple Linear Regression Analysismentioning
confidence: 99%
“…Lower job satisfaction will jeopardize work motivation, and may even impact primary health work negatively as a whole ( Meng et al, 2009 Gili et al, 2016 ). Many empirical studies on medical staff have identified that job satisfaction is negatively related to turnover intention ( Mobley, 1977 ; Xu et al, 2013 ; Chen et al, 2015 ; Gualano et al, 2016 ; Zhang and Fang, 2016 ; Han et al, 2018 Ding et al, 2021 ). Village doctors report higher job satisfaction and retention rate ( Chen et al, 2015 ; Zhang and Fang, 2016 ; Zhang, 2018 Gu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%